Identification friend or foe being the story of aircraft recognition - Hamilton, Tim (HMSO, 1994)
"Identification friend or foe began as a political expedient during the First World War but, despite the lessons learned, its vital significance wasn't fully realised until late 1941 when pressure was applied to save allied lives from 'friendly fire'. This book, designed and written by author/film director Tim Hamilton, traces for the very first time the complex history of aircraft recognition. Extracting from official documents, complete with all their political meanderings, and from 'restricted' service publications, it exposes both the successes and the tragic mistakes which have coloured the development of aircraft recognition from 1914 until the wind-down in 1946"--P. [4] of cover.